(untitled) (Fiep Bulletin - online, 2013)
This research aims to analyze the velocity curve in competing school finalists in the sprint of the 75 meter dash of the 56th Games Student spring, participated in the experiment 16 athletes at school level the region of Ponta Grossa – Parana, Brazil, and eight athletes were male and eight female athletes aged between 13 and 14 years. To speed the analysis was performed with a camera filming a video of the Panasonic Model No. AG-DVC20P - Mini DV - NTSC using the method "panning" in the course of 75 meters, the video camera was positioned within 37.5 meters of the start of the race height of the ground 2.20 meters, with a distance of 40 meters from the race course, were placed 17 cones arranged every 5 meters of the race course. Later the images were edited in the PC and evaluated the velocity of the athletes at every 5 meters with precision in hundredths of time, using as reference the chest of the athlete to cross the lines of cones arranged on the race course. After analysis of the images were obtained the following results: that athletes of both sexes had a marked acceleration until about 40 meters with values ??of 6.08 m/s boys and 6.98 m/s girls, after this distance was a slight increase in acceleration until the end of the path 6.63 m / s girls and boys with 7.47 m / s. In this way related athletes in this study should go a distance of 66.60 meters, just 40 meters would be 60% of the race, leaving only 26.60 meters which would be 40% to finish the race. Considering the results suggest a distance of 65 meters for distance more appropriate to see what would be the fastest competitors in the sprint.